Influence of thermal and solvent annealing on the morphology and photovoltaic performance of solution processed, D–A–D type small molecule-based bulk heterojunction solar cells. Issue 113 (2nd November 2015) - Kumar, C. H. Pavan; Ganesh, K.; Suresh, T.; Sharma, Abhishek; Bhanuprakash, K.; Sharma, G. D.; Chandrasekharam, Malapaka
Abstract : Four new small moleculesCSDPP9–CSDPP12 were obtained with appended electron donating units in the molecular terminals of a DPP core. On solvent and thermal annealing, for theCSDPP11 :PC71 BM blend, the BHJ device displayed a PCE of 5.47%. Abstract : Four new solution-processable donor–acceptor–donor (D–A–D) structured organic small molecules (CSDPP9, CSDPP10, CSDPP11 andCSDPP12 ) with diketopyrrolopyrrole (DPP) as the central core unit and different electron donating groups as the terminal units, were designed and synthesized. These molecules employed as donors along with PC71 BM as an electron acceptor in solution processed bulk heterojunction (BHJ) solar cells, exhibited a strong visible (450–650 nm) absorption band with suitable molecular orbital energy levels. OSCs based on these small molecules achieved moderate power conversion efficiency (PCE) in the range of 2.86–3.55% along with high open circuit voltage ( V oc ) and the difference is correlated with the different electron donating units used in the DPP. The observed high open circuit voltage ( V oc ) of the device is directly related to the HOMO energy level of the DPP. The BHJ devices, based onCSDPP11 :PC71 BM andCSDPP12 :PC71 BM subjected to solvent and thermal annealing showed improved PCEs of 5.47% and 4.88% respectively. The enhancement in the PCE has been attributed to the improved charge carrier mobility, crystallinity and light harvesting ability of the active layer.